Neraca kehidupan dan parameter demografi Henosepilachna vigintioctopunctata Fabricius (Coleoptera: Coccinellidae) pada empat tanaman inang berbeda - Waskito, Adi; Atmowidi, Tri; Kahono, Sih (Jurnal Entomologi Indonesia, 2018)
Ladybird beetle, Henosepilachna vigintioctopunctata Fabricius (Coleoptera: Cocinellidae) has a wide host plants belonging to family of Solanaceae. The species can be a serious pests of solanaceous crops, such as, eggplants and potatoes. The aims of the research were to study life table and to measure demography parameters of H. vigintioctopunctata fed by leaves of Solanum torvum, S. nigrum, S. melongena, and Brugmansia suaveolens. Results showed that the highest longevity (68.7 days, male and 79 days, female) occurred in H. vigintioctopunctata fed by leaves of  S. nigrum, followed by S. torvum (20.6 days, male and 31.7 days, female), S. melongena (1.5 days, male and 2.5,0 days, female, and B. suaveolens (1.8 days, male and 1.7 days, female). Based on demography parameters, the highest net reproductive rate occured in H. vigintioctopunctata fed on leaves of S. torvum (R0 = 2.11 individu), followed by S. nigrum (R0 = 0.64 females/female), S. melongena (R0 = 0.06 females/female), and B. suaveolens (R0 = 0.006 females/female). Generation time was high in H. vigintioctopunctata fed by S. nigrum (28.53 days) and S. torvum (27.42 days) compared to S. melongena (5,9 days) and B. suaveolens (2.5 days). Intrinsic growth rate of H. vigintioctopunctata was highest in S. torvum (r = 0.0094 females/female/day). Based on the life table and demography parameters, S. torvum is the most suitable plant for growth and development of H. vigintioctopunctata.